Propensión a la innovación tecnológica de las empresas manufactureras peruanas que no desarrollan actividades de Investigación y Desarrollo (I&D) - Del Carpio Gallegos, Javier Fernando (2019)
More emphasis should be given to companies that do not carry out research and development activities. In this regard, this research has set as objectives to analyze the relationship between non-technological innovations and technological innovations; the second objective, analyze how activities not related to investment in research and development, allow the development of technological innovations; The third objective is focused on analyzing how external knowledge sources are associated with technological innovations in low and medium technological intensity companies (L&LMT) Based on a sample of 834 Peruvian L&LMT manufacturing companies, and through the implementation of a logistic regression model PROBIT the hypothesis were analyzed, it was confirmed that non-technological innovations influence technological innovations, that many activities such as the acquisition of machinery favor the propensity in technological innovations, concluding that L&LMT companies should encourage those activities not necessarily linked to research and development to make technological innovations.